Development Strategy Pembelajaran Pendidikan Agama Islam Sekolah Formal - Lukman Nul Hakim; Ahmad Aziz Fanani; Ahmad Ihwanul Muttaqin (Nusantara Journal of Islamic Studies, 2022)
The existence of Islamic Religious Education in SMP Negeri 2 Jember has not changed the situation much. This is due to the dichotomy of education system, caused by general lessons that subordinate Islamic Religious Education, so that religious teachers lose the guts to continue to develop Islamic Religious Education strategies, even if sometimes the potential exists. So there needs to be a form of a reliable strategy, in order to attract students' interest in learning religion. In this regard, the discussion in this journal discusses the school's strategy in developing Islamic education at SMP Negeri 2 Jember. The research method used in this research is qualitative. This research is a case study, because this research is carried out intensively, in detail and fundamentally about an institution that projects educational development strategies. The results of this study indicate that SMP Negeri 2 Jember concentrates on learning PAI. This is evidenced by the various efforts made for the success of school strategies in improving PAI learning in public schools on a macro basis.